2015
DOI: 10.1016/j.jobaz.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

A multiparameter investigation into adverse effects of aflatoxin on Oreochromis niloticus health status

Abstract: Aflatoxin is a common contaminant of foods, particularly in the staple diets of many developing countries. To evaluate adverse effects of aflatoxin B1 (AFB1) toxicity on health status in the Nile tilapia Oreochromis niloticus, fish were fed diet contaminated with either 20 or 100 ppb AFB1 for 6 or 12 weeks. Growth indices, survival rate and hepatosomatic index (HSI) were assessed. Blood samples were collected for hematological profiles (e.g. RBCs and WBC count, Hb content). Liver enzyme activity; aspartate ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 53 publications
11
44
0
1
Order By: Relevance
“…The same problem has been reported in varied species of farmed aquaculture [3]. Aflatoxins are polyketide secondary-derived metabolites produced by strains of Aspergillus flavus and Aspergillus parasiticus [1].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The same problem has been reported in varied species of farmed aquaculture [3]. Aflatoxins are polyketide secondary-derived metabolites produced by strains of Aspergillus flavus and Aspergillus parasiticus [1].…”
Section: Introductionsupporting
confidence: 61%
“…Thus, the increased activity of AST and ALT could be an appropriate mechanism to increase free amino acids to accelerate detoxification process. An increase in AST and ALT is reported in various tissues of rats [32,33] and Nile tilapia, Oreochromis niloticus, [3] treated with aflatoxin B1.…”
Section: Discussionmentioning
confidence: 99%
“…Our result showed no change on hematological parameters (RBC, WBC, PCV, Hb and MCV ) as well as the percentage of Lymphocytes, Neutrophils and Monocytes. Mahfouz and Sherif [39] demonstrated that hematological profiles and monocytes, esinophils, and lymphocytes were influenced by the dose and duration of exposure to AFB1 contaminated diet. As RBC, WBC, PCV, Hb and MCV levels were significantly decreased in the high AFB1 exposed group.…”
Section: Effects Of Varying Doses Of Dietary Biotoxin and Aflatoxin Omentioning
confidence: 99%
“…An increase of these enzyme activities in the extracellular fluid or serum is a sensitive indicator of even minor cellular damage [41] in which cellular enzymes are released from the cells into the blood serum, which in turn indicates stress-based tissue impairment. Mahfouz and Sherif [39] showed that the activity of serum AST, ALT and ALP liver enzymes significantly increased in tilapia exposed to 100 ppb AFB1. Also, Mahfouz and Sherif [39] verified that AST, ALT and ALP were significantly increased in the serum of rats administered AFB1 (250 μg/kg/day for 2 weeks) indicating the presence of damaged and dysfunctional liver cells.…”
Section: Effects Of Varying Doses Of Dietary Biotoxin and Aflatoxin Omentioning
confidence: 99%
See 1 more Smart Citation